Fine‐scale spatial genetic structure analysis of the black truffle Tuber aestivum and its link to aroma variability. (28th July 2015) - Molinier, Virginie; Murat, Claude; Frochot, Henri; Wipf, Daniel; Splivallo, Richard
Summary: Truffles are symbiotic fungi in high demand by food connoisseurs. Improving yield and product quality requires a better understanding of truffle genetics and aroma biosynthesis. One aim here was to investigate the diversity and fine‐scale spatial genetic structure of the Burgundy truffle T uber aestivum . The second aim was to assess how genetic structuring along with fruiting body maturation and geographical origin influenced single constituents of truffle aroma. A total of 39 Burgundy truffles collected in two orchards were characterized in terms of aroma profile (SPME‐GC/MS) and genotype (microsatellites). A moderate genetic differentiation was observed between the populations of the two orchards. An important seasonal and spatial genetic structuring was detected. Within one orchard, individuals belonging to the same genet were generally collected during a single season and in the close vicinity from each other. Maximum genet size nevertheless ranged from 46 to 92 m. Geographical origin or maturity only had minor effects on aroma profiles but genetic structuring, specifically clonal identity, had a pronounced influence on the concentrations of C8 ‐ and C4 ‐VOCs. Our results highlight a high seasonal genetic turnover and indicate that the aroma of Burgundy truffle is influenced by the identity of single clones/genets.